LexArt Words for Painting (France, Germany, England, The Netherlands, 1600-1750) - Heck, Michèle-Caroline (Théorie des Arts, 2018)
LexArt. Words for Painting is a dictionary of terms and concepts used by the painters and theorists to describe both practice and theory in France, Germany, England and the Netherlands in the 17th and 18th centuries. The purpose is to highlight the stakes of the usages of these words and concepts in different chronological and geographical contexts. 77 essays cover nearly 250 concepts. The entries, appearing in traditional alphabetical order, outline the boundaries of a new reading of the painting as seen through the eye of the painter as well as through the eye of the spectator. Indeed, the "speaking painting" not only invites the spectator into the painter's studio to show how the painting is done, but introduces him to the painting itself, indicating what to see and how to see.